Estimated Economic Benefits of Reducing Low Birth Weight in Low-Income Countries - Alderman, Harold; Behrman, Jere R. (World Bank, Washington, DC, 2013)
The paper reviews the evidence on the link between low birth weight (LBW) and health outcomes and economic productivity. The overall benefits depend both on the economic environment and the manner in which future streams of income are discounted. Thus, the sensitivities of the overall estimates to different discount rates and to different assumptions about each of the component estimates are explored. Under plausible assumptions for low income countries, the economic benefits from reducing LBW are fairly substantial, on the order of magnitude of about $580 per infant moved from the LBW to non LBW category. Varying the assumptions used will affect the total as well as the relative share of the seven categories, but under most assumptions the benefits far exceed the costs of known interventions.